2009
DOI: 10.1111/j.1744-7917.2009.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of MtCOI polymerase chain reaction‐restriction fragment length polymorphism in differentiating between Q and B whitefly Bemisia tabaci biotypes

Abstract: The invasive, insecticide-resistant, Q whitefly biotype, has gradually spread to other countries including the US via human-mediated movement of plant materials. We assessed the utility of the VspI-based mtCOI (mitochondrion cytochrome oxidase I) polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique as a rapid, cost-effective, and reliable alternative for differentiating the Q from the dominant B biotype in Arizona. Using the standard mtCOI gene sequencing and mtCOI PCR-RFLP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…PCR ampliÞcations began with 94ЊC denaturation for 3 min, followed by 35 cycles of 94ЊC denaturation for 1 min, 52ЊC annealing for 1 min, and 72ЊC extension for 2 min, and a Þnal 72ЊC extension for 10 min. Half of each PCR products were used to differentiate MED from MEAM1 by using VspI-based mtCOI PCR-RFLP (Ma et al 2009). When a sample was identiÞed as a MED individual by VspI-based mtCOI PCR-RFLP (Ma et al 2009), the remaining half of its PCR products were then digested at 37ЊC for 2 h with 2 U of AluI, a restriction endonuclease that cleaves DNA at AGCT sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR ampliÞcations began with 94ЊC denaturation for 3 min, followed by 35 cycles of 94ЊC denaturation for 1 min, 52ЊC annealing for 1 min, and 72ЊC extension for 2 min, and a Þnal 72ЊC extension for 10 min. Half of each PCR products were used to differentiate MED from MEAM1 by using VspI-based mtCOI PCR-RFLP (Ma et al 2009). When a sample was identiÞed as a MED individual by VspI-based mtCOI PCR-RFLP (Ma et al 2009), the remaining half of its PCR products were then digested at 37ЊC for 2 h with 2 U of AluI, a restriction endonuclease that cleaves DNA at AGCT sites.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 120 mtCOI sequences (545 bp) were generated by sequencing the mtCOI PCR products of the MED samples detected in Arizona during 2004Arizona during Ð2008 (27 in 2004Arizona during , 30 in 2006Arizona during , 27 in 2007Arizona during , and 35 in 2008 as described in Ma et al (2009). In addition to the 120 MED mtCOI sequences, 1,839 worldwide B. tabaci mtCOI sequences in total, including from the United States, were retrieved from GenBank (http://www.ncbi.nlm.nih.gov/) on 21 March 2011.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PCR-RFLP was reported as a simple, quick, cost-effective and reliable alternative method to distinguish B. tabaci species (Khasdan et al 2005;Ma et al 2009;Chu et al 2012). This method was applied to support results of sequence analysis and differentiating the MED and MEAM1 species of B. tabaci populations.…”
Section: Vspi-based Mtcoi Polymerase Chain Reaction (Pcr)-restrictionmentioning
confidence: 99%
“…The main genetic techniques were allozymes (Gunning et al 1997), RAPD PCR (randomly amplified polymorphic DNA polymerase chain reaction) (De Barro and Driver 1997), AFLP (amplified fragment length polymorphism) (Cervera et al 2000), rITS1 (ribosomal integenic transcribed spacer 1) (De Barro et al 2000) and mitochondrial DNA markers, mt16s and mtCo1) ( Frohlich et al 1999;Ma et al 2009). From the above studies of the phylogenetic characteristics of B. tabaci biotypes, De Barro et al (2011) have listed 36 identified biotypes worldwide.…”
Section: Classification Of Bemisia Tabaci B Biotypementioning
confidence: 99%